Identification of specific foods responsible for inflammation in children with eosinophilic esophagitis successfully treated with empiric elimination diet - Kagalwalla, Amir F; Shah, Ameesh; Li, B U K; Sentongo, Timothy A; Ritz, Sally; Manuel-Rubio, Maria; Jacques, Katie; Wang, Deli; Melin-Aldana, Hector; Nelson, Suzanne P (Journal of pediatric gastroenterology and nutrition, 2011)
Eosinophilic esophagitis (EoE) is an immune-mediated chronic inflammatory disorder triggered by food antigen(s). A 6-food elimination diet (SFED) excluding cow's milk, soy, wheat, egg, peanuts/tree nuts, and seafood has been shown to induce remission in a majority of children with EoE. The goal of the present study was to identify specific food antigens responsible for eosinophilic esophageal inflammation in children with EoE who had achieved histological remission with the SFED. In this analysis, we retrospectively analyzed children with EoE who completed subsequent single-food reintroductions that led to identification of foods causing disease recurrence. Repeat upper endoscopy with biopsies was performed after single-food introductions. Recurrence of esophageal eosinophilia following a food reintroduction identified that food antigen as a cause of EoE. A total of 36/46  (25 M/11F) children who were initially successfully treated with SFED completed this trial; the mean age was 7.6  ±  4.3 years. The most common foods identified were 25 to cow's milk (74%), 8 to wheat (26%), 4 to eggs (17%), 3 to soy (10%), and 1 to peanut (6%). Milk was 8 times more likely to cause EoE compared with wheat, the next most common food (95% confidence interval 2.41-26.62, P = 0.0007). Serial single-food reintroductions following induction of histological remission with the SFED can lead to the identification of specific causal food antigen(s) in EoE. Cow's milk was the most common food identified in subjects with EoE treated with SFED. A subset of children with EoE may develop tolerance to their food sensitivities while on the SFED.